Utilisation of wood biomass residues from fruit tree branches, evergreen hardwood shrubs and Greek fir wood as raw materials for particleboard production. Part A. Mechanical properties - Lykidis, Charalampos; Grigoriou, Athanasios; Barboutis, Ioannis (Wood Material Science & Engineering, 2014)
Abstract This paper investigates the potential of utilising wood biomass from fruit tree branches and evergreen hardwood shrubs as raw materials in the production of particleboards when mixed with Greek fir wood particles. The main mechanical properties of the boards made therefrom were determined and compared with those made of typical industrial wood (IW) particles. The highest modulus of rupture and elasticity (30.0 N/mm2 and 4330 N/mm2, respectively) in bending and screw withdrawal (SW) resistance (127.8 N/mm) were reported for boards made of Greek fir and were downgraded when the fruit tree branches or evergreen hardwood shrub particles also participated. The participation of fruit tree branch particles in proportions higher than 50% improved the internal bond (IB) of fir produced boards, while the highest IB strength (0.95 N/mm2) was reported for boards made of fruit tree branches. Particleboards made of evergreen hardwood shrubs showed inferior mechanical properties compared with those made of IW particles. The latter also showed superior bending strength but inferior SW resistance compared with boards made of fruit tree branches. Hygroscopic and other properties are under determination and will be presented and discussed in the second part of the work.
doi: 10.1080/17480272.2013.875589
Keywords: evergreen hardwood shrubs; fruit tree branches; Greek fir; mechanical properties; particleboard

Evergreen Mediterranean hardwoods as particleboard raw material - Barboutis, John a.; Philippou, John L (Building and Environment, 2007)
Wood and biomass (branches and foliage) of ﬁve Mediterranean evergreen hardwood species (Quercus coccifera, Quercus ilex, Arbutus unedo, Phillyrea latifolia, Erica arborea) growing in Greece were investigated as particleboard raw material. The average diameter of the stems varied between the species from 4.1 cm (Erica arborea) to 7.5 cm (Quercus ilex) and the bark to wood ratio of the stems varied between the species from 7.8% (Quercus ilex) to 15.9% (Erica arborea). Bulk density of particleboard furnishes produced by processing the above materials through a chipper and a ring ﬂaker varied between the species from 143.6 to 162.5 kg/m 3 . Common industrial furnish reached in the used lab conditions a bulk density of 143 kg/m 3 . Particle size and their distribution also varied between the hardwood species. One-layer laboratory particleboards made with the above materials at densities of 650, 700 and 750 kg/m 3 had considerable lower mechanical properties but better dimensional stability than boards made with common industrial furnish. All properties were affected by wood species and board density. Internal bond of all boards was higher than the value required by EN 319/1993 but adequate bending strength at moderate densities (0.70 kg/m 3 ) was achieved only in boards made with Arbutus unedo and Quercus ilex. Boards made with branches and foliage had very low mechanical properties.
Keywords: biomass; mediterranean evergreen hardwoods; particleboard

Evergreen Mediterranean hardwoods as particleboard raw material - Barboutis, John a; Philippou, John L. (Building and Environment, 2007)
Wood and biomass (branches and foliage) of ﬁve Mediterranean evergreen hardwood species (Quercus coccifera, Quercus ilex, Arbutus unedo, Phillyrea latifolia, Erica arborea) growing in Greece were investigated as particleboard raw material. The average diameter of the stems varied between the species from 4.1 cm (Erica arborea) to 7.5 cm (Quercus ilex) and the bark to wood ratio of the stems varied between the species from 7.8% (Quercus ilex) to 15.9% (Erica arborea). Bulk density of particleboard furnishes produced by processing the above materials through a chipper and a ring ﬂaker varied between the species from 143.6 to 162.5 kg/m 3 . Common industrial furnish reached in the used lab conditions a bulk density of 143 kg/m 3 . Particle size and their distribution also varied between the hardwood species. One-layer laboratory particleboards made with the above materials at densities of 650, 700 and 750 kg/m 3 had considerable lower mechanical properties but better dimensional stability than boards made with common industrial furnish. All properties were affected by wood species and board density. Internal bond of all boards was higher than the value required by EN 319/1993 but adequate bending strength at moderate densities (0.70 kg/m 3 ) was achieved only in boards made with Arbutus unedo and Quercus ilex. Boards made with branches and foliage had very low mechanical properties.
Keywords: biomass; mediterranean evergreen hardwoods; particleboard